LAUGHTER INTERJECTION IN INDONESIAN ON WHATSAPP SOCIAL MEDIA - Dewi Nurmala; Tengku Silvana Sinar (IKIP Siliwangi, 2022)
The objective of the research is to seek the laughter interjection on WhatsApp social media. The data is taken from the conversations on WhatsApp social media. The data are analyzed using Natural Semantic Metalanguage (NSM) theory. The method used is a qualitative method. From the results of the study, it was found that there were several laughter interjections found in WhatsApp social media, namely laughter interjections hahaha, hehehe, wkwkwk, and hiks hiks hiks. The interjection of laughing hahaha indicates a sense of reluctance or discomfort and there is also a sense of humor felt by the speaker. While the laughter interjection hehehe shows the shame towards someone or feels bad because the speaker feels disturbing to others or feels reluctant to treat the interlocutor in the conversation. Then there is the laughter interjection wkwkwk which shows something that is considered very funny so that the speaker or interlocutor feels amused by the stated expression. Finally, there is an interjection of laughing hiks hiks hiks, which is a person's embarrassment about a statement of someone has said. Keywords: Laughter Interjection, WhatsApp, Natural Semantic Metalanguage